Hisab Awal Bulan Hijriyah dalam Kitab “Al-Khulashoh Al-Wafiyah” - Sayful Mujab (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2020)
One of the methods developed and used as a reference by Indonesian Muslim scholars is the early reckoning of the Islamic month which is contained in the book al-Khulashoh al-Wafiyah. This article aims to examine how the initial hijriyah reckoning in al-Khulashoh al-Wafiyah. This study is included in the domain of literature review with a qualitative approach. The results of the study show that the hijriyah calendar that applies to Muslims is based on the position of the moon on the earth and sun. The movement of the moon to the earth is relatively constant every year, so that these data can be used as a reference for predicting the position of the moon on earth and the sun. The prediction of the height of the new moon becomes a reference in determining the hijriyah calendar.  AbstrakSalah satu metode yang berkembang dan dijadikan acuan oleh cendekiawan muslim Indonesia adalah hisab awal bulan hijriyah yang terdapat dalam kitab al-Khulashoh al-Wafiyah. Artikel ini bertujuan mengkaji tentang bagaimana hisab awal hijriyah dalam al-Khulashoh al-Wafiyah. Kajian ini termasuk dalam ranah kajian kepustakaan dengan pendekatan kualitatif. Hasil kajian menunjukkan bahwa kalender hijriyah yang berlaku bagi umat Islam didasarkan kepada posisi bulan terhadap bumi dan matahari. Pergerakan bulan terhadap bumi relatif tetap pada setiap tahunnya, sehingga data-data tersebut dapat dijadikan  sebagai acuan untuk prediksi posisi bulan terhadap bumi dan matahari. Prediksi ketinggian hilal ini menjadi acuan dalam penentuan kalender hijriyah.